Artemisinin and partner drug resistance markers in Plasmodium falciparum from Tanzanian paediatric malaria patients, 2016–2022 - Aveline Assey; Silvia Scialabba; Maria Mgella Zinga; Philip Koliopoulos; Welmoed van Loon; Caroline A. Minja; Britta Groendahl; Johannes Plett; Stephan Gehring; Mariam M. Mirambo; Neema Kayange; Frank P. Mockenhaupt; et al. (Malaria Journal)
Abstract Background Plasmodium falciparum malaria remains a significant public health concern in Tanzania, particularly among children under 5 years of age. The emergence and spread of partial artemisinin resistance in East Africa add to this concern. Specific mutations in the P. falciparum kelch-13 (Pfk13) and multidrug drug resistance 1 (Pfmdr1) genes are associated with artemisinin resistance and lumefantrine tolerance, respectively. The emergence of antimalarial drug resistance may be associated with unstable transmission in sub-Saharan Africa (SSA). Time-trends of Pfk13 and Pfmdr1 mutations as well as the multiplicity of infection (MOI) as a proxy for transmission intensity were investigated. Methods Between 2016 and 2022, 173 P. falciparum PCR-positive samples were collected from febrile inpatient and outpatient children aged 3 months to 18 years at selected health facilities in Mwanza, Tanzania. Pfk13 and Pfmdr1 were amplified by PCR and Sanger-sequenced. Polymorphic Pfmsp1 and Pfmsp2 allelic markers were genotyped by nested PCR in 168 samples to assess MOI. Results Among 143 samples successfully sequenced for Pfk13, 7.0% (10/143) exhibited non-synonymous mutations including the WHO-validated artemisinin resistance marker R561H in 1.4% (2 patients, 2022). As for Pfmdr1, the wild-type N86 allele was observed in 100% (97/97) of isolates, and about half (55/97) carried the wild-type Y184 allele. The mean multiplicity of infection (MOI) was 1.5, and did not change significantly over time. Single-genotype and polyclonal infections were observed in 59.3% (80/135), and 40.7% (55/135) respectively. Conclusion This study from Mwanza, Tanzania demonstrates the presence of a validated artemisinin resistance marker Pfk13 R561H in 2022 and suggests increased lumefantrine tolerance. MOI as a proxy marker of endemicity was low and stable over the six years of observation. The detection of these resistance markers reinforces the need for continuous genetic surveillance to sustain the efficacy of antimalarial therapies in paediatric patients.